(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2022)
Ensuring the safe transfusion of blood and its derivatives for the recipient remains a very urgent problem of modern transfusion medicine. Despite the existing achievements in this area, unfortunately, it is still not possible to completely secure blood transfusions for the recipient. The tasks of the Blood Services of all countries of the world without exception include ensuring the safety of donated blood and its components for patients receiving transfusions in clinics. An absolute priority is to ensure infectious safety in relation to bloodborne infections, among which viral hepatitis is the most common. Diagnosis of hepatitis B and C at the present level is mandatory both in Uzbekistan and abroad. At the same time, it should be emphasized that it is in the Blood Service that the most modern diagnostic methods with maximum sensitivity are used. Donor blood transfusion worldwide, an average of 0.01-2% of donors are carriers of hepatitis viruses. Therefore, at present, donor blood is examined for the presence of hepatitis viruses before transfusion to the recipient. The risk of infection increases in individuals who need repeated blood transfusions or blood products [3,4].